Le bilinguisme judiciaire dans les juridictions fédérales - Patry, Réjean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This article examines in detail the bilingual system of justice presently in effect in Canada's federal courts. The author first discusses the effect ot the Official Languages Act (1969) and the recent constitutional reforms on the status of the French and English languages before the nation's courts. He affirms that both languages are indeed equal in the eyes of the law — in theory, at least. In practice, however, he shows that this balance is slightly modified